Cadaveric Testing of Robot-Assisted Access to the Internal Auditory Canal for Vestibular Schwannoma Removal. Issue 3 (March 2017) - Dillon, Neal P.; Balachandran, Ramya; Siebold, Michael A.; Webster, Robert J.; Wanna, George B.; Labadie, Robert F.
Abstract : Hypothesis: An image-guided robotic system can safely perform the bulk removal of bone during the translabyrinthine approach to vestibular schwannoma (VS). Background: The translabyrinthine approach to VS removal involves extensive manual milling in the temporal bone to gain access to the internal auditory canal (IAC) for tumor resection. This bone removal is time consuming and challenging due to the presence of vital anatomy (e.g., facial nerve) embedded within the temporal bone. A robotic system can use preoperative imaging and segmentations to guide a surgical drill to remove a prescribed volume of bone, thereby preserving the surgeon for the more delicate work of opening the IAC and resecting the tumor. Methods: Fresh human cadaver heads were used in the experiments. For each trial, the desired bone resection volume was planned on a preoperative computed tomography (CT) image, the steps in the proposed clinical workflow were undertaken, and the robot was programmed to mill the specified volume. A postoperative CT scan was acquired for evaluation of the accuracy of the milled cavity and examination of vital anatomy. Results: In all experimental trials, the facial nerve and chorda tympani were preserved. The root mean squared surface accuracy of the milled cavities ranged from 0.23 to 0.65 mm and the milling time ranged from 32.7 to 57.0 minute. Conclusion: This work shows feasibility of using a robot-assisted approach for VS removal surgery. Further testing and system improvements are necessary to enable clinical translation of this technology.